Sentencing rape : a comparative analysis - Brown, Graeme (Lawyer) (Oxford [England] : Hart, 2020)
"This book presents an in-depth comparative study of sentencing practice for rape in six common law jurisdictions: England and Wales, Scotland, Ireland, Canada, New Zealand, and South Africa. It provides a thorough review of the medical literature on the physical and psychological effects of rape; the legal and philosophical literature on the seriousness of the offence; and the victim's role in sentencing. Given the increasingly common practice of perpetrators using mobile and online technologies to record or photograph the commission of sexual offences, the book examines recent socio-legal research on technology-facilitated sexual violence and considers the implications for sentencing. Building on recent scholarship on judicial decision-making in sentencing and case law comprising over 250 decisions of the relevant appellate courts, the book explores and critically analyses judicial approaches to rape sentencing. The analysis is undertaken with a view to suggesting possible reforms to rape sentencing in 'non-guideline' jurisdictions. In so doing, this book seeks to establish general principles for sentencing rape, assisting in the imposition of proportionate sentences"--
Sentencing Rape : An Introduction to the Study -- The Seriousness of Rape and the Victim's Role in Sentencing -- Technology-Facilitated Sexual Violence and Image-Based -- Sexual Abuse : the Filming of Rape and Sexual Assault -- From Guidance to Guidelines : Rape Sentencing in England and Wales -- A 'Radically Different' Approach : Rape Sentencing in Scotland -- Proportionality and Individualised Justice : Rape Sentencing in the Republic of Ireland -- 'Pragmatism and Individualisation' versus 'The Mandatory Minimums Algorithm' : Rape Sentencing in New Zealand and South Africa -- Principled Discretion in Rape Sentencing.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Rape -- Law and legislation -- English-speaking countries; Sentences (Criminal procedure) -- English-speaking countries; Criminal law & procedure; Electronic books